A current-reuse dual-channel bio-signal amplifier for WBAN nodes. (December 2017) - Liu, Lianxi; Zhang, Yi; Song, Yu; Zhu, Zhangming; Yang, Yintang
Abstract: This paper presents a dual-channel low-noise bio-signal amplifier for the low-power wireless body area network (WBAN) nodes. A dual-channel three-input current-reuse (DTCR) structure is proposed to optimize the noise performance of amplifier. The chopper-stabilized technique is employed to reduce 1/f noise and the offset voltage. Moreover, a high input impedance is achieved by using the pre-charge technique. In addition, a DC offset canceling loop is employed to suppress the electrode offset. The proposed amplifier is implemented in a standard 0.18 μm CMOS process with an active area of about 0.68 × 0.73 mm 2 . The experimental results demonstrate that an input referred noise of 1.12 μVrms has been achieved over a bandwidth from 0.35 Hz to 150 Hz. The total power consumption of each channel is about 1.44 μW at the supply voltage of 1.2 V. And the amplifier achieves an input impedance of about 200 MΩ, a CMRR of 111 dB at 50 Hz and a PSRR of 87.5 dB at 50 Hz.